2′, 3′-cAMP treatment mimics the stress molecular response in Arabidopsis thaliana. Issue 4 (19th January 2022) - Chodasiewicz, Monika; Kerber, Olga; Gorka, Michal; Moreno, Juan C; Maruri-Lopez, Israel; Minen, Romina I; Sampathkumar, Arun; Nelson, Andrew D L; Skirycz, Aleksandra
Abstract: The role of the RNA degradation product 2′, 3′-cyclic adenosine monophosphate (2′, 3′-cAMP) is poorly understood. Recent studies have identified 2′, 3′-cAMP in plant material and determined its role in stress signaling. The level of 2′, 3′-cAMP increases upon wounding, in the dark, and under heat, and 2′, 3′-cAMP binding to an RNA-binding protein, Rbp47b, promotes stress granule (SG) assembly. To gain further mechanistic insights into the function of 2′, 3′-cAMP, we used a multi-omics approach by combining transcriptomics, metabolomics, and proteomics to dissect the response of Arabidopsis ( Arabidopsis thaliana ) to 2′, 3′-cAMP treatment. We demonstrated that 2′, 3′-cAMP is metabolized into adenosine, suggesting that the well-known cyclic nucleotide–adenosine pathway of human cells might also exist in plants. Transcriptomics analysis revealed only minor overlap between 2′, 3′-cAMP- and adenosine-treated plants, suggesting that these molecules act through independent mechanisms. Treatment with 2′, 3′-cAMP changed the levels of hundreds of transcripts, proteins, and metabolites, many previously associated with plant stress responses, including protein and RNA degradation products, glucosinolates, chaperones, and SG components. Finally, we demonstrated that 2′, 3′-cAMP treatment influences the movement of processing bodies, confirming the role of 2′, 3′-cAMP in the formation and motility of membraneless organelles. Abstract : 2′, 3′-cAMP induces changes in plant cells that correspond to changes induced by stress.